Randomized Phase II Trial of Seribantumab in Combination with Erlotinib in Patients with EGFR Wild‐Type Non‐Small Cell Lung Cancer. (12th April 2019) - Sequist, Lecia V.; Gray, Jhanelle Elaine; Harb, Wael A.; Lopez‐Chavez, Ariel; Doebele, Robert C.; Modiano, Manuel R.; Jackman, David Michael; Baggstrom, Maria Quintos; Atmaca, Akin; Felip, Enriqueta; Provencio, Mariano; Cobo, Manuel; et al.
Abstract: Background: Seribantumab (MM‐121) is a fully human IgG2 monoclonal antibody that binds to human epidermal growth factor receptor 3 ( HER3/ErbB3 ) to block heregulin ( HRG/NRG )‐mediated ErbB3 signaling and induce receptor downregulation. This open‐label, randomized phase 1/2 study evaluated safety and efficacy of seribantumab plus erlotinib in advanced non‐small cell lung cancer (NSCLC). Here, we report the activity of seribantumab plus erlotinib, versus erlotinib alone, in patients with EGFR wild‐type tumors and describe the potential predictive power of HRG. Materials and Methods: Patients with EGFR wild‐type NSCLC were assigned randomly to receive seribantumab + erlotinib or erlotinib alone. Patients underwent pretreatment core needle biopsy and archived tumor samples were collected to support prespecified biomarker analyses. Results: One hundred twenty‐nine patients received seribantumab + erlotinib ( n = 85) or erlotinib alone ( n = 44). Median estimated progression‐free survival (PFS) in the unselected intent‐to‐treat (ITT) population was 8.1 and 7.7 weeks in the experimental and control arm, respectively (hazard ratio [HR], 0.822; 95% confidence interval [CI], 0.37–1.828; p = 0.63), and median estimated overall survival was 27.3 and 40.3 weeks in the experimental and control arm, respectively (HR, 1.395; 95% CI, 0.846 to 2.301; p = .1898) In patients whose tumors had detectable HRG mRNA expression, treatment benefit was observed in the seribantumab + erlotinib combination (HR, 0.35; 95% CI, 0.16–0.76; p = .008). In contrast, in patients whose tumors were HRG negative, the HR was 2.15 (95% CI, 0.97–4.76; p = .059, HRG‐by‐treatment interaction, p value = .0016). Conclusion: The addition of seribantumab to erlotinib did not result in improved PFS in unselected patients. However, predefined retrospective exploratory analyses suggest that detectable HRG mRNA levels identified patients who might benefit from seribantumab. An ongoing clinical trial of seribantumab, in combination with docetaxel, is underway in patients with advanced NSCLC and high HRG mRNA expression (NCT02387216). Abstract : This article reports the results of a group of patients in a phase II study that assessed the combination of seribantumab and erlotinib in non‐small cell lung cancer patients whose tumors were EGFR wild‐type.